2007
DOI: 10.1016/j.dsx.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

People awareness about diabetes disease and its complications among aged 18 years and older in Bushehr port inhabitants (Iran)

Abstract: SummaryIntroduction: One of the most prevalent metabolic disease is diabetes and it can lead to enormous medical as well as socio-economic consequences.The Iranian diabetes population is estimated to be around 1.5 million. Studies show that approximately half of the people with type 2 diabetes (T2DM) are undiagnosed and thus unaware that they have the disease. This lack of awareness can lead to presentation with complications and its consequences.The aim of this survey was to determine the level of population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 5 publications
4
14
1
1
Order By: Relevance
“…Another interesting finding of our study was the relative high awareness of diabetes among female participants as compared to males. These results contradict the findings of a Pakistani and an Iranian study [17,23] because both studies reported female participants as less aware of diabetes than males. The possible reason behind more female awareness was the difference in culture, geographical area, health seeking behavior, relatively high literacy rate and the female population having more attachment to their family members.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Another interesting finding of our study was the relative high awareness of diabetes among female participants as compared to males. These results contradict the findings of a Pakistani and an Iranian study [17,23] because both studies reported female participants as less aware of diabetes than males. The possible reason behind more female awareness was the difference in culture, geographical area, health seeking behavior, relatively high literacy rate and the female population having more attachment to their family members.…”
Section: Discussioncontrasting
confidence: 83%
“…A 48-itemed study instrument that consisted of total five sections (A, B, C, D and E) was developed after extensive literature review [17,[22][23][24][25]. Section-A contained 6 questions that were related to respondent's demography (age, gender, education, residence, family history and family income were independent variables of the study).…”
Section: Study Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, about one quarter of the participants did not know the causes of diabetes. In previous studies, it has been reported that only a few respondents were able to give a rudimentary definition of diabetes as well as its causes, signs and consequences [20,21] . This shows that there is a considerable level of knowledge from respondents on diabetes since this is one of the most common non-communicable diseases and people are particularly showing great level of interest about the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless about one quarter of the participants did not know the causes of diabetes. In previous studies elsewhere, it was reported that only a few respondents were able to give a rudimentary definition of diabetes as well as its causes, signs and consequences [22,23]. This shows that there is a considerable level of knowledge of the respondents on diabetes since this is one of the commonest non-communicable diseases and people are particularly showing great level of interest in knowing about the disease in order to avoid getting it.…”
Section: Knowledge Level About Dm2mentioning
confidence: 99%